Development of a method for geometrical modeling of the airfoil profile of an axial turbomachine blade - Borisenko, Valeriy; Ustenko, Serhiy; Ustenko, Iryna; Kuzma, Kateryna (Eastern-European Journal of Enterprise Technologies, 2019)
A method for geometric modeling of the contours of the suction and the pressure side profiles of axial turbomachine blades described by compound curves and formed by two sections has been proposed. Each section of the profile contour was modeled by a curve described in a natural parameterization. The cubic law of curvature distribution was applied to the leading sections of the profile and square law was used for the trailing section. Juncture of the leading and trailing sections of the profiles of the suction and the pressure side was provided with smoothness of the third order which assumes equality of values of functions, function derivatives, curvature and curvature derivatives in the junction point. When modeling the blade profile, thirteen kinematic and geometric parameters were used. Unknown coefficients of the square and cubic laws of distribution as well as lengths of the profile arcs of the suction and the pressure side sections were determined in the process of modeling the profile cascade for specified parameters. The problem was solved by minimizing deviations of the plotted curves from the reference points of the modeled profile located in the throat of the blade channel and on the circle, which determines maximum thickness of the profile. Based on the proposed method, a program code was developed which in addition to the digital information on the modeled turbomachine blade profile displays the results in a graphical form on a computer screen. The calculation studies confirmed feasibility of the proposed advanced method of modeling the suction and the pressure side profiles of axial turbine blades. The developed method can be useful in organizations engaged in the design and manufacture of blades of axial gas turbines of gas turbine engines